Collinear Three-Photon Excitation of a Strongly Forbidden Optical Clock Transition - Samuel P. Carman; Jan Rudolph; Benjamin E. Garber; Michael J. Van de Graaff; Hunter Swan; Yijun Jiang (姜一君); Megan Nantel; Mahiro Abe; Rachel L. Barcklay; Jason M. Hogan (Physical Review X)
The ^{1}S_{0}-^{3}P_{0} clock transition in strontium serves as the foundation for the world’s best atomic clocks and for gravitational wave detector concepts in clock atom interferometry. This transition is weakly allowed in the fermionic isotope ^{87}Sr but strongly forbidden in bosonic isotopes. Here, we demonstrate coherent excitation of the clock transition in bosonic ^{88}Sr using a novel collinear three-photon process in a weak magnetic field. We observe Rabi oscillations with frequencies of up to 50 kHz using W/cm^{2} laser intensities and Gauss-level magnetic field amplitudes. The absence of nuclear spin in bosonic isotopes offers decreased sensitivity to magnetic fields and optical lattice light shifts, enabling atomic clocks with reduced systematic errors. The collinear propagation of the laser fields permits the interrogation of spatially separated atomic ensembles with common laser pulses, a key requirement for dark matter searches and gravitational wave detection with next-generation quantum sensors.